An Incidentally Detected Venous Malformation of the Uterine Cervix: Case Report - Yeşim Bayoğlu Tekin; Recep Bedir; Emine Seda Güvendağ Güven (Medical Network, 2016)
Venous malformations of the uterine cervix are extremely rare. Most lesions are asymptomatic and incidental, however sometimes, they may present with abnormal vaginal bleeding. We aimed to describe a case of venous malformation of the uterine cervix and discuss the differential diagnosis and clinical management of this entity.